Educational modules as an effort to increase knowledge of cardiovascular disease risk prevention - Solihah, Ii (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: Heart disease is no longer affecting the elderly, but more and more young people are getting heart disease. An educational approach in health promotion by using attractive media is one of the most necessary ways to invite teenagers to behave in a healthy life. The purpose of this study was to determine the effect of the education module on knowledge of risk factors for cardiovascular disease prevention. The research method used a quasi-experimental design with a control group. The research sample is students at SMK Era Pembangunan 3, West Jakarta. Sampling was done by simple random sampling and a total sample of 68 people were selected. Data were analyzed using chi square test and multiple logistic regression. The results showed that the education module given to respondents could increase students’ knowledge in preventing cardiovascular disease risk factors with a p value of 0.000:OR 51.83 (95% CI 9.84-273.05). Conclusion: the education module has an effect on increasing knowledge about the prevention of cardiovascular disease risk factors. Recommendations are expected that future research will develop more instruments on risk factors for cardiovascular disease.